ANALISIS PERBANDINGAN KINERJA GURU BERSERTIFIKAT DAN NON SERTIFIKAT DALAM PELAKSANAAN PEMBELAJARAN - Agus Tristiana; Holilulloh Holilullah; Muhamad Mona Adha (Jurnal Kultur Demokrasi, 2012)
This study uses a descriptive method that aims to provide an accurate picture of the material and the observed phenomena. Subjects in this study were 28 Bandar Lampung SMP teachers either certified or not certified with a sample of 42 people. Data collection using questionnaire technique. The results were analyzed using t-test and the percentage formula. the results showed that the performance of teachers who have been certified tend to be better than the performance of teachers who have not certified that can be seen from the percentages. in both categories of teachers who have been certified performance greater than the performance of teachers who have not been certified that 67% of teachers who have been certified and 53% for teachers who are not certified teachers, while for the medium category which has been certified by 15% and  certified teachers who have not 20% then to bad category as much as 18% for teachers who have been certified and 27% for teachers who have not been certified. Based on statistical calculations there is a comparison between the performance of teachers who are certified and non certified in the implementation of learning with t count t table that is equal to 97.33 2.02.Keywords: certification, teacher performance, implementation of learning